SOUTH AFRICAN SOCIAL POLICY ‘TOKENISM’ AS AUSTERITY GRIPS - Bond, Patrick (Africanus: Journal of Development Studies, 2016)
The South African government’s mandate was to transform state social policy and correct historic class, racial, gendered and other injustices. The main design patterns of economic and social policy during the 1990s and 2000s, however, can be characterised respectively as ‘neoliberal’ (insofar as they favour the market) and ‘tokenistic’ (insofar as that part of the society that is not served by the market is provided only a small fraction of what it requires to live a decent life). The state has sufficient resources and could tax or prevent profit outflows that would allow surpluses to be redistributed. But as part of a more general tendency to ‘talk left, walk right’, the ruling party has declined to engage in substantive redistribution, risking the ire of its constituencies. The rise of left opposition forces coincides with a new top-down commitment to austerity, one that already began to fray by mid-2016. Only when those forces become more coherent, potentially by the time of the 2019 national election, will a full accounting of the damage of tokenistic social policy be possible, as part of a systemic effort to reverse course.